Razgrom nemetskikh voisk pod Moskvoi . The Defeat of Nazi Troops Near Moscow – aka Moscow Strikes Back - Varlamov, Leonid; Kopalin, Ilya (Central Newsreel Studio, 1942)
The film is based on documentaries showing Moscow and the Moscow region and people digging defense trenches, defense factories' selfless work, severe fighting, and the liberation of towns and villages near the capital. It is a story about the heroism people demonstrated defending the capital, but it also portrays the scale of destruction and loss. A total of two million troops, 2.700 tanks, and 2.000 aircraft were engaged in the mortal combat near Moscow in late 1941. The battle of Moscow was Hitler's first defeat. By pushing Nazi troops back by 150 to 400 kilometers, the Red Army staved off the threat on the Soviet capital and it also drastically changed the situation on the front.